Role of the Environment Digital Work and Career Development on Employee Performance with Organizational Commitment as Intervening Variables - Ahmad Dzulfikri Budi Kusworo (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Study This aim For analyze influence environment digital work and development career to performance employee with commitment organization as intervening variables . Research use approach quantitative with method survey against 150 employees company services and technology in Indonesia. Environment digital work becomes factor important in the modern world of work because organization the more depend on technology , system hybrid work , applications digital collaboration , and flexibility work . On the other hand , development career also plays a role important in increase loyalty and commitment employee to organization . Data analysis techniques used is multiple linear regression and mediation test use Sobel test or SEM-PLS approach . Research results expected show that environment digital work and development career influential positive to commitment organization and performance employees . In addition , the commitment organization estimated mediate connection between environment digital work and development career to performance employee. Findings study This expected give contribution theoretical for development modern HR literature and contributions practical for organization in designing digital workplace policies and development a better career effective. Environment work and development career has proven influence performance , but the impact often more​ strong when through commitment organization .